2023
DOI: 10.1002/anie.202309897
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Photosensitizer Controlled Reactions of 4‐Hydroxycoumarins and Unactivated Olefins: Hydroarylation and Subsequent [2+2] Cycloaddition

Rui Chang,
Yubing Pang,
Juntao Ye

Abstract: Herein, we report a photoinduced approach for hydroarylation of unactivated olefins using 4‐hydroxycoumarins as the arylating reagent. Key to the success of this reaction is the conversion of nucleophilic 4‐hydroxycoumarins into electrophilic carbon radicals via photocatalytic arene oxidation, which not only circumvents the polarity‐mismatch issue encountered under ionic conditions but also accommodates a broad substrate scope and inhibits side reactions that were previously observed. Moreover, divergent react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 124 publications
0
1
0
Order By: Relevance
“…In 2023, Ye et al also reported catalytic α-alkylation reactions of 4-hydroxycoumarins with nonactivated alkenes (Scheme 18). [73] A combination of a dicyanopyrazine-derived organophotocatalyst, DPZ (56), and 2,4,6-triisopropylbenzenethiol (TRIPSH, 57) was used, and high yields were obtained in methanol under blue-LED irradiation. A SET process proceeded between the coumarin, which contains an enol structure of 1,3dicarbonyl compounds, and the photocatalyst to form a radical intermediate for the reaction.…”
Section: α-Alkylation Reactions Via Photoactivationmentioning
confidence: 99%
“…In 2023, Ye et al also reported catalytic α-alkylation reactions of 4-hydroxycoumarins with nonactivated alkenes (Scheme 18). [73] A combination of a dicyanopyrazine-derived organophotocatalyst, DPZ (56), and 2,4,6-triisopropylbenzenethiol (TRIPSH, 57) was used, and high yields were obtained in methanol under blue-LED irradiation. A SET process proceeded between the coumarin, which contains an enol structure of 1,3dicarbonyl compounds, and the photocatalyst to form a radical intermediate for the reaction.…”
Section: α-Alkylation Reactions Via Photoactivationmentioning
confidence: 99%